Job Prospect and Intention on Tax Consultant Profession - Ria Sandra Alimbudiono; Aulia Wahyu Wardhani (BAJ: Behavioral Accounting Journal, 2022)
This study aimed to investigate accounting students' perceptions of job prospects and their intention in becoming tax consultants at University X. This study employed an exploratory qualitative approach. Questionnaires were distributed to all accounting students at University X to determine research participants. Twenty students were willing to engage in this study. The data collection was collected by means of interviews for 40 minutes. The results showed that the majority of students' perceptions of job prospects were influenced by people's opinion, including parents, teachers, siblings, friends, and even family friends. While the remaining was influenced by internet, social media, experience, working place and community’s point of view. Besides, the factor that enhance the students’ intention in becoming tax consultant were the passion on tax consultant profession itself, result expectation, and self-efficacy. Hence for further study, it was advised to investigate the discrepancy in tax application between Java and regions outside of Java island that required actions from relevant authorities.